Поетичні функції онімів світової та української міфології у творах неокласиків - Місінькевич, Олеся; Misinkevych, Olessia (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено власним чоловічим іменам світової та української міфології, функціонування яких у поетичних творах неокласиків є необхідною умовою для повного розкриття змісту та окремих аспектів тексту. Вибір власного імені для позначення певної особи є важливим, оскільки саме цей процес дає змогу найкраще визначити всі аспекти позначуваного онімом слова.The article is dedicated to men’s proper names world and Ukrainian mythology, the functioning of which in lyrics of newclassics is the obligatory condition for fullness of the plot and some aspects of the text. The choice of proper name name for indications of certain person is important as just process gives the opportunity to determine all the aspects of indicating onimom words. Interpretation of key mifonimov of masculine is Given, the features of functioning of appearances are studied in the dynamics of individual artistic-vivid smyslotvorchestva. A conclusion is done that cultural-aesthetic maintenance of key poetic nominations in works of neoclassicisms testifies to universality of mythology as komponenta of conceptual model of the world. Cultural-aesthetic maintenance of key poetic nominations (proper names, mifoobrazov of world and Ukrainian culture) confirms the special value of onyms for the language picture of the world.
Poetic Functions of Onyms of World and Ukrainian Mythology in Works of Neoclassic
Keywords: неокласичний текст; поетична онімія; архетипна свідомість; міфонім; анторопонім; neoclassical text; poetic onymation; archetypal consciousness; mifonim; antroponim